Assessment of soil characteristics and the productive potential of native Poaceae forage species in the Central Highlands of Peru - Arias Arredondo, Alberto (2025)
Given the increasing pressure on natural grassland ecosystems in the Peruvian high Andes, optimizing the use of native forage species has become essential for understanding the relationship between soil characteristics and the productive potential of these plants. This study evaluated the relationship between soil properties and the produc tive potential of three native forage species: Festuca dolichophylla, Cinnagrostis vicunarum, and Jarava ichu. The research was conducted in natural grasslands in the district of Yauli, province of Yauli, department of Junin, at approximately 4000 m.a.s.l. During the dry season 2023, soil samples were collected following standardized protocols, and key soil parameters were analyzed. The nutritional characteristics of the forage species were also assessed, including dry matter content, total protein, calcium, phosphorus, in vitro organic matter digestibility, and metabolizable energy. The results revealed significant differences among species. Festuca dolichophylla exhibited the highest protein content (10.7%), superior digestibility (52.5%), and greater metabolizable energy (8.4 MJ∙kg-1), making it the most suitable forage option for livestock in the highland ecosystem over 4000 m.a.s.l., where en vironmental factors constrain agricultural activity. In contrast, Cinnagrostis vicunarum and Jarava ichu showed lower protein levels, with Jarava ichu displaying particularly low digestibility (28.9%) and energy content (4.6 MJ∙kg-1), limiting its productive potential despite its high dry matter yield. These findings provide a strong scien tific foundation for developing sustainable grassland management strategies in the Peruvian Andes, supporting the implementation of agronomic practices that enhance forage productivity while contributing to biodiversity conser vation. Moreover, this study highlights the importance of soil characterization as a key tool for optimizing forage resource utilization in high-altitude farming systems, facilitating informed decision-making in land management and environmental remediation policies.